Molecular and physiological consequences of faulty eukaryotic ribonucleotide excision repair. (12th December 2019) - Kellner, Vanessa; Luke, Brian
Abstract: The duplication of the eukaryotic genome is an intricate process that has to be tightly safe‐guarded. One of the most frequently occurring errors during DNA synthesis is the mis‐insertion of a ribonucleotide instead of a deoxyribonucleotide. Ribonucleotide excision repair (RER) is initiated by RNase H2 and results in error‐free removal of such mis‐incorporated ribonucleotides. If left unrepaired, DNA‐embedded ribonucleotides result in a variety of alterations within chromosomal DNA, which ultimately lead to genome instability. Here, we review how genomic ribonucleotides lead to chromosomal aberrations and discuss how the tight regulation of RER timing may be important for preventing unwanted DNA damage. We describe the structural impact of unrepaired ribonucleotides on DNA and chromatin and comment on the potential consequences for cellular fitness. In the context of the molecular mechanisms associated with faulty RER, we have placed an emphasis on how and why increased levels of genomic ribonucleotides are associated with severe autoimmune syndromes, neuropathology, and cancer. In addition, we discuss therapeutic directions that could be followed for pathologies associated with defective removal of ribonucleotides from double‐stranded DNA. Abstract : Kellner and Luke review how RNase H2 or topoisomerase enzymes remove misincorporated ribonucleotides from genomic DNA, and the relevance of such mechanisms for both malignant and autoimmune diseases such as Aicardi–Goutières syndrome.